2010
DOI: 10.1074/jbc.m109.083493
|View full text |Cite
|
Sign up to set email alerts
|

Wilms Tumor Suppressor 1 (WT1) and Early Growth Response 1 (EGR1) Are Regulators of STIM1 Expression

Abstract: Store-operated calcium entry (SOCE) is a key evolutionarily conserved process whereby decreases in endoplasmic reticulum Ca 2؉ content lead to the influx of Ca 2؉ across the plasma membrane. How this process is regulated in specific tumor cell types is poorly understood. In an effort to address this concern, we obtained and tested primary Wilms tumor cells, finding no detectable SOCE in this cell type. Analysis of the expression levels of STIM1 and ORAI1 (the molecular mediators of SOC) revealed poor STIM1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 41 publications
(40 reference statements)
2
66
0
Order By: Relevance
“…The first of these does not contact the bases (Stoll et al 2007) and contributes little to specificity (Hamilton et al 1995;Nakagama et al 1995). Consequently, WT1 binds the same consensus sequence as Egr1/Zif268 (Stoll et al 2007) and, in some cases, antagonizes Egr1/Zif268 function (Ritchie et al 2010). For the work described here, we used a construct of WT1 containing only ZnF2 through ZnF4, which was structurally analogous to Egr1/Zif268.…”
Section: Resultsmentioning
confidence: 99%
“…The first of these does not contact the bases (Stoll et al 2007) and contributes little to specificity (Hamilton et al 1995;Nakagama et al 1995). Consequently, WT1 binds the same consensus sequence as Egr1/Zif268 (Stoll et al 2007) and, in some cases, antagonizes Egr1/Zif268 function (Ritchie et al 2010). For the work described here, we used a construct of WT1 containing only ZnF2 through ZnF4, which was structurally analogous to Egr1/Zif268.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, STIM1 and Orai1 were shown to play an important role in breast cancer cell migration and metastasis using the MDA-MB231 ER Ϫ cell model (46). Ritchie et al demonstrated that STIM1 gene expression in primary Wilms tumors is reciprocally regulated by Wilms tumor suppressor 1 (WT1) and early growth response 1 (EGR1) (47). The expression and role of STIM/Orai isoforms in ER ϩ breast cancer progression is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms directing Ca 2ϩ -dependent PMCA induction in these different systems are presently unknown. Induction of the ER calcium sensors STIM1 and STIM2 is mediated by Erg1-binding sites present in their promoters and follows calcium entry and CREB phosphorylation (61). Because STIM proteins and the Ca 2ϩ -selective Orai1 channel form the molecular substrate for store-operated calcium entry, their induction upon T cell activation represents another example of Ca 2ϩ -dependent transcriptional regulation of calcium homeostasis.…”
Section: Regulation Of Sodium/calcium Exchangers and Calcium Pumpsmentioning
confidence: 99%